Functional Radiotherapy Targeting using Focused Dose Escalation. Issue 10 (October 2015) - Alonzi, R.
Abstract Various quantitative and semi-quantitative imaging biomarkers have been identified that may serve as valid surrogates for the risk of recurrence after radiotherapy. Tumour characteristics, such as hypoxia, vascularity, cellular proliferation and clonogen density, can be geographically mapped using biological imaging techniques. The potential gains in therapeutic ratio from the precision targeting of areas of intrinsic resistance makes focused dose escalation an exciting field of study. This overview will explore the issues surrounding biologically optimised radiotherapy, including its requirements, feasibility, technical considerations and potential applicability.